Mathematical representation ability viewed from the students' cognitive style in Two Stay Two Stray with product assessment - Khairunnisa, Muthia; Masrukan, Masrukan (Department of Mathematics, Universitas Negeri Semarang, 2020)
The mathematical representation ability in Junior High School 1 Bojong is still not optimal. For this reason, one of the methods that can be used to increase the ability of mathematical representation is cooperative learning type Two Stay Two Stray with product assessment. This research aims to obtain the effectiveness of learning and analyze students' mathematical representation abilities in terms of the reflective-impulsive cognitive style. This research used Mixed Methods with Explanatory Sequential Design. The population in this study was all 8th graders of Junior High School 1 Bojong, while two classes were obtained as samples using cluster sampling techniques. For the qualitative analysis, four students were selected purposively. Data collection techniques used observation, documentation, tests, and interviews. The results showed that: (1) Two Stay Two Stray learning with product assessment is effective on the achievement of students' mathematical representation abilities, (2) subjects showed various mathematical representation ability.